Towards Adaptive Sensor-cloud for Internet of Things - I Made Murwantara; Hendra Tjahyadi; Pujianto Yugopuspito; Arnold Aribowo; Irene A. Lazarusli (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
The emerge of the Internet of Things (IoT) data as a commodity to optimize public services such as Fishing Locator has made sensor-cloud an important object. When sensors that are members of multiple IoT gateways can inter-operate at the same time for more than one application, it will reduce cost to deploy IoT infrastructure. However, reliability has also developed as the most important aspect for real-time data collection that should be streamed constantly. Due to uncertainty factors sensors failure is potentially occurred, then an adaptive approach should be addressed into this as to guarantee the flow of streaming data. This paper proposed an adaptive sensor-cloud mechanism to manage the reliability by using a runtime model approach where a transition model and dynamic software product line engineering will take place to weaving the system. Our technique is comparable to other approaches and can be implemented in many types of Cloud-based services.